Cytotoxic steroidal saponins from the roots and rhizomes of Maianthemum henryi. Issue 11 (3rd June 2021) - Zhang, Xin; Sun, Jing; Zhang, Xiaofei; Zhang, Shuo; Zhang, Xuan; Xue, Xuanji; Guo, Zengjun
Abstract: Henryiosides F and G (1 and 2 ), two new steroidal saponins along with two known analogues (3 and 4 ) were obtained from the roots and rhizomes of Maianthemum henryi . Their structures were determined by physicochemical properties and spectroscopic methods including 1D, 2D-NMR, IR and HR-ESI-MS data analysis. Cytotoxic activity in human HepG2 and SW620 tumour cells were evaluated by the MTT method and all of the saponins exhibited cytotoxicity with IC50 values ranging from 15.33 μ M to 57.85 μ M. Graphical Abstract: UF0001